2017
DOI: 10.18203/issn.2454-5929.ijohns20173052
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of smartphone based app with free field hearing for possible use as a screening test

Abstract: <p class="abstract"><strong><span lang="EN-US">Background:</span></strong>Hearing loss is an invisible injury that has been viewed as an acceptable by-product of military service. It is imperative to detect hearing loss at early stage to take immediate remedial measures. In Indian armed forces the current method of assessment of hearing is primarily by Free Field Hearing which is obsolete and has numerous shortcomings. We contucted a study using free iOS application to detect hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…All of the studies included were published between 2015 and 2020. Nine apps were found: uHear (22)(23)(24)(25) , uHearing Test (25) , EarScale (26) , HearScreen (27,28) , HearingTest (29,30) , Digits-in-Noise Test (10,(31)(32)(33)(34) , hearTest (35,36) , Free Field Hearing (FFH) (37) , Free Hearing Test (37) . The most investigated apps were Digits-in noise Test (5 articles) and uHear (4 articles).…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies included were published between 2015 and 2020. Nine apps were found: uHear (22)(23)(24)(25) , uHearing Test (25) , EarScale (26) , HearScreen (27,28) , HearingTest (29,30) , Digits-in-Noise Test (10,(31)(32)(33)(34) , hearTest (35,36) , Free Field Hearing (FFH) (37) , Free Hearing Test (37) . The most investigated apps were Digits-in noise Test (5 articles) and uHear (4 articles).…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…All apps found in this study used pure tone as the auditory stimulus (23)(24)(25)(26)(27)(28)(29)(30)(35)(36)(37) , except for Digits-in-Noise Test (10,(31)(32)(33)(34) , which used speech stimulation through digits and Free field hearing (FFH) (37) which used words.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…It was reported that the hearing check app was more sensitive than the conventional voice test (98% and 73%). 21 We report that in our study FFCT has a more standard way of examination with constant broadband sounds produced in correspondence to pure tone average. This differs from FFVT as there was a lack in the standardization of speech sound levels of the examiners.…”
Section: Discussionmentioning
confidence: 68%
“…The test retest reproducibility measured with Pearson correlation coefficient was high (0.99) with hearing check application [14].…”
Section: Discussionmentioning
confidence: 91%